PEMANFAATAN PENDEKATAN BIOMEKANIKA UNTUK MENGURANGI RISIKO CEDERA PADA PEMBELAJARAN PENDIDIKAN JASMANI - Ahmad Mursyidin; Annisa Salsabila; Muhamad Fahmi Hidayat; Riski Aditya; Andi Mandasini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Physical education is an important component in developing students' physical competence. However, inappropriate movement patterns during physical education learning pose a significant risk of injury. This study aims to analyze the application of biomechanical approaches in reducing injury risk in physical education learning. The method used is a systematic literature review by reviewing 25 relevant research articles published between 2020 and 2025. The results show that a biomechanical approach that includes analysis of movement patterns, kinematics, kinetics, and neuromuscular control can significantly reduce the risk of injury by up to 42% in physical education activities. The implementation of biomechanical principles in the design of physical education learning focuses on three main aspects: load distribution, center of gravity, and muscle activation during movement. The findings indicate that teachers who apply biomechanical approaches in lesson planning produce safer and more effective learning environments. It is concluded that the biomechanical approach is a scientifically proven and applicable strategy to reduce the risk of injury in physical education learning contexts. Keywords: biomechanics, injury prevention, physical education, movement patterns, kinematics